Protocol for conducting a single-cell sequencing assay for transposase-accessible chromatin analysis - Wen Ma; Peiyao Ma; Yue Yuan; Dandan Hu; Kaifeng Li; Pengfei Cai; Chuanyu Liu (STAR Protocols)
Summary: While the single-cell sequencing assay for transposase-accessible chromatin (scATAC-seq) is a powerful single-cell resolution tool for studying chromatin accessibility, its analytical workflow presents significant challenges for researchers new to scATAC-seq. Here, we present a protocol for conducting scATAC-seq analysis using a publicly available dataset as an example. We describe steps for data pre-processing and downstream analysis. We then detail procedures for computational multi-omics integration. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.